A Research Proposal of Inventory Management System for Red Camia Supermarket: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This project's primary goal is to maximise profit and minimise the cost to the client, and will be focusing on the inventory management system of the supermarket. The developers chose the inventory management system because it is an integral part of a supermarket that can affect the firm's net profit or loss. The method used in the project is the System Development Life Cycle (SDLC) method, wherein the developers used the following steps: project planning, system analysis, project development, implementation, and maintenance. The developers interviewed the supermarket owner, where we conducted the project and analysed the problems that needed to be solved to maximise the client's profit. The results of the system visualise that most of the parts of the inventory management system are currently functional. The IT specialist needs to finalise the additional parts that are still a prototype. Based on the proposed inventory management system, the ensuing discussion states that the research has solved the following problems: 1.) Inaccurate level of monitoring; 2.) Unmonitored expiration date; 3.) Problem on reports; 4.) Loss due to theft; and 5.) Lack of trend forecasting.